The Influence of Islamic-Based Leadership on Employee Performance: Employee Engagement as A Mediation Variable - Nada Arina Romli; Almirin Syićraz (IAIN Syekh Nurjati Cirebon, 2025)
Performance is an important factor in the success of an organization or company. Performance can be defined as the work results of individuals in terms of quality and quantity, achieved by an employee in carrying out their duties and fulfilling responsibilities within a specific period. Performance refers to the work results achieved by an individual or group within an organization, in accordance with their respective authorities and responsibilities, to attain organizational goals legally, without violating laws, and adhering to norms and ethics. Leadership plays an important role in improving employee performance in a company. This is exemplified by the Islamic leadership style, rooted in the era of Prophet Muhammad SAW, which is characterized by four key traits: Shidiq (truthfulness), Amanah (trustworthiness), Fatonah (wisdom), and Tabligh (conveying truth). This study aims to test the direct and indirect influence of Islamic leadership traits on employee performance with employee engagement as a mediating variable. This study uses an explanatory research method with primary data. Research data were collected through an online questionnaire, namely Google Forms. The results of the study showed that all Islamic leadership traits (Shidiq, Amanah, Fatonah, and Tabligh) have a direct positive effect on employee performance. This means that when leaders can apply Islamic leadership traits well, employee performance will also be good in their work. However, employee engagement as a mediating variable is only able to mediate one of the leadership traits on employee performance, namely, Shidiq.